Lean Green Tendency - Cláudia Sousa e Silva; Sara Azevedo; Maria Fonseca (Brazilian Journal of Operations & Production Management)
Lean philosophy and Green practices have been identified as management approaches that allow organizations to reach better economic and environmental results. Nevertheless, some authors argue that results can be enhanced with the integration of the Lean and Green practices. This synchronous effort has led to the developing a new Lean philosophy branch, the Lean Green.